Relationship of Serum Cholesterol Levels to Atopy in the U.S. Population - Fessler, Michael B. (2009)
BACKGROUND: Cholesterol promotes Th2 immunity and allergic inflammation in rodents; whether this occurs in humans is unclear. Reports of both direct and inverse associations between serum cholesterol and atopy in different populations suggest that race and/or other demographic variables may modify these relationships. AIMS OF THE STUDY: To determine relationships between levels of three serum cholesterol measures (total cholesterol [TC], high density lipoprotein-cholesterol [HDL-C], and non-HDL-C), and atopy in a sample representative of the U.S. population. METHODS: Cross-sectional study of 6,854 participants aged ≥6 years from the 2005-2006 National Health and Nutrition Examination Survey. RESULTS: In the overall population, adjusted odds ratios (AORs) per 2-standard deviation increase of TC and non-HDL-C for biochemical atopy (defined as ≥1 allergen-specific IgE to 19 allergens) were 1.17 (95% confidence interval [CI], 1.00-1.38) and 1.19 (95% CI, 1.03-1.39), respectively. Interactions by race were noted for the two relationships (interaction p=0.004 and p=0.009, respectively), with non-Hispanic Whites (NHWs) having direct relationships (TC: AOR 1.27 [95% CI, 1.03-1.57]; non-HDL-C: AOR 1.27 [95% CI, 1.03-1.56]) and non-Hispanic Blacks (NHBs) inverse relationships (TC: AOR 0.77 [95% CI, 0.62-0.95]; non-HDL-C: AOR 0.86 [95% CI, 0.69-1.08]). The adjusted HDL-C-atopy relationship was nonsignificant for NHWs and inverse for NHBs (AOR 0.77 [95% CI, 0.61-0.96]). Relationships were independent of body mass index and serum C-reactive protein, and unmodified by corticosteroid or statin usage. Results were similar using current hay fever/allergy as the atopy outcome. CONCLUSIONS: There are marked inter-racial differences in the relationship between serum cholesterol and atopy in the U.S population.